Acute systemic loss of Mad2 leads to intestinal atrophy in adult mice - Klaske M. Schukken (Nature Portfolio, 2021)
Abstract Chromosomal instability (CIN) is a hallmark of cancer, leading to aneuploid cells. To study the role that CIN plays in tumor evolution, several mouse models have been engineered over the last 2 decades. These models have unequivocally shown that systemic high-grade CIN is embryonic lethal. We and others have previously shown that embryonic lethality can be circumvented by provoking CIN in a tissue-specific fashion. In this study, we provoke systemic high-grade CIN in adult mice as an alternative to circumvent embryonic lethality. For this, we disrupt the spindle assembly checkpoint (SAC) by alleviating Mad2 or truncating Mps1, both essential genes for SAC functioning, with or without p53 inactivation. We find that disruption of the SAC leads to rapid villous atrophy, atypia and apoptosis of the epithelia of the jejunum and ileum, substantial weight loss, and death within 2–3 weeks after the start of the CIN insult. Despite this severe intestinal phenotype, most other tissues are unaffected, except for minor abnormalities in spleen, presumably due to the lower proliferation rate in these tissues. We conclude that high-grade CIN in vivo in adult mice is most toxic to the high cell turnover intestinal epithelia.